A microsimulation analysis of the distributional impact over the three waves of the COVID-19 crisis in Ireland - Cathal O'Donoghue; Denisa M. Sologon; Iryna Kyzyma; John McHale (University of Essex, Centre for Microsimulation and Policy Analysis (CeMPA), 2021)
This paper relies on a microsimulation framework to undertake an analysis of the distributional implications of the COVID-19 crisis over three waves. Given the lack of real-time survey data during the fast moving crisis, it applies a nowcasting methodology and real-time aggregate administrative data to calibrate an income survey and to simulate changes in the tax benefit system that attempted to mitigate the impacts of the crisis. Our analysis shows how crisis-induced income-support policy innovations combined with existing progressive elements of the tax-benefit system were effective in avoiding an increase in income inequality at all stages of waves 1-3 of the COVID-19 emergency in Ireland. There was, however, a decline in generosity over time as benefits became more targeted. On a methodological level, our paper makes a specific contribution in relation to the choice of welfare measure in assessing the impact of the COVID-19 crisis on inequality.
Keywords: 330; Public Policy; Welfare Benefits; Taxation; Covid-19; Health; Microsimulation; Income Dynamics